Penerapan Discovery Learning Mengggunakan Puzzle Kolaborasi untuk Meningkatkan Hasil Belajar dan Kerja Sama Peserta Didik Kelas VII SMPN 29 Surabaya - Lismawati, Rina; Murtini, Sri; Sriviyantiningrum, Nurul (Universitas Pahlawan Tuanku Tambusai, 2024)
The objective of this research is to enhance learning outcomes and collaboration among students using the discovery learning model through collaborative puzzles. The study was conducted in Class VII B at SMP Negeri 29 Surabaya. This research is a collaborative classroom action research that includes planning, implementation, observation, and reflection. The results of this study indicate that the percentage of learning outcomes increased from Cycle I to Cycle II. The average score in Cycle I was 77.94, while in Cycle II it increased to 88.38. The percentage of classical completeness in Cycle I was 61.76%, whereas in Cycle II, it increased to 88.23%. Collaboration among students also improved across all groups. All groups showed improvement in Cycle II compared to Cycle I. The implementation of the discovery learning model using collaborative puzzle media can enhance both collaboration and learning outcomes.